KONSEP PENATAAN TAMAN BMW SEBAGAI RUANG TERBUKA PUBLIK DI STADION JIS, JAKARTA - Bisri, Choliel; Herlambang, Suryono (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2024)
BMW Park or Wibawa Human Park is a park built by PT Jakarta Propertindo which is still located inside the JIS stadium. This park has an area of ​​2.02 hectares and functions as a public open space and as a sports facility and recreation area. The park began construction on March 14 2019 by the Governor of Jakarta Anies Baswedan who started construction. After three years of running, JIS was finally completed in 2022. BMW Park in the afternoon is usually used as a sports facility such as jogging, gymnastics and skateboarding. The main problem with this park is that the facilities and green open space are still few and the standard of the park as a public open space provided is still inadequate in accordance with the guidelines and provision and use of public open space according to the Minister of Public Works Number 05/PRT/M/2004. The location of the park is just an empty area with a few seats and minimal trees so the weather around the location of this object still feels hot during the day. The small number of trees and the large amount of empty land that has not been filled make this park feel very hot during the day and there is still minimal shade. The small vehicle parking capacity and limited number of toilets mean that this BMW park is not yet included in the criteria for a park as a public open space that meets standards and is adequate. Keywords: arrangement; park; public open space Abstrak Taman BMW atau Taman Manusia Wibawa merupakan taman yang dibangun oleh PT Jakarta Propertindo yang lokasinya masih terdapat didalam stadion JIS. Taman ini memiliki luas 2,02 hektare dan memiliki fungsi sebagai ruang terbuka publik dan sebagai sarana olahraga maupun tempat rekreasi. Taman mulai dibangun pada 14 Maret 2019 oleh Gubernur Jakarta Anies Baswedan memulai pembangunannya. Setelah tiga tahun berjalan, JIS akhirnya selesai pada tahun 2022. Taman BMW pada sore hari biasa digunakan sebagai sarana olahraga seperti joging, senam, dan bermain skateboard. Masalah pokok dari taman ini yaitu mengenai fasilitas dan ruang terbuka hijau yang masih sedikit dan standar taman sebagai ruang terbuka publik yang disediakan masih belum memadai sesuai dengan pedoman dan penyediaan dan pemanfaatan ruang terbuka publik menurut Menteri Pekerjaan Umum Nomor 05/PRT/M/2004. Lokasi taman hanya seperti lahan kosong dilengkapi beberapa tempat duduk dan pepohonan yang masih minim sehingga cuaca di sekitar lokasi objek ini masih terasa panas di siang hari. Jumlah pepohonan yang sedikit dan banyaknya lahan yang masih kosong belum terisi menjadikan taman ini terasa sangat panas bila di siang hari serta tempat peneduh yang masih minim. Kapasitas parkir kendaraan yang kecil, serta jumlah toilet yang terbatas membuat Taman BMW ini belum masuk ke dalam kriteria taman sebagai ruang terbuka publik yang memenuhi standar dan memadai.